Optimization Study of Diameter, Length, Filter Hole, and Engine Speed in Modified Exhaust on Power and Noise Level of 110 cc Motorcycle - Susilo, Sugeng Hadi; Anantya, Muhammad Zulfikar Rizky; Yusof, Hazlina Md (Evrimata: Journal of Mechanical Engineering, 2024)
The muffler functions to reduce noise. Changes in the muffler design can also affect engine performance and the environmental impact due to noise. In densely populated urban environments, the high noise level from motor vehicles can disturb the surrounding community. The purpose of this study are as follows: 1) To understand the influence of changes in muffler diameter, pipe length, and filter hole on power. 2) To understand the influence of changes in muffler diameter, pipe length, and filter hole on noise levels. 3) To determine the optimal values obtained from changes in muffler diameter, pipe length, and filter hole diameter. The study method is a two-stage experiment. The first stage aims to determine pressure values and flow velocities to identify the optimal values for muffler design. The second stage aims to determine power and noise levels to assess the effects of the muffler design changes.Based on the conducted study, there are effects from changes in muffler diameter, pipe length, and filter hole diameter on the generated engine power. The highest power output was obtained at the variable of 50 mm muffler diameter, 425 mm pipe length, and 2 mm filter hole diameter. As for the impact on noise levels, the lowest noise level was recorded at the variable of 38 mm muffler diameter, 525 mm pipe length, and 2 mm filter hole diameter. The optimal values were obtained through muffler design changes with a diameter of 45 mm, pipe length of 475 mm, and a 2 mm filter hole diameter